Streptococcus agalactiae in pregnancies complicated by preterm prelabor rupture of membranes. (2nd April 2016) - Musilova, Ivana; Pliskova, Lenka; Kutova, Radka; Jacobsson, Bo; Paterova, Pavla; Kacerovsky, Marian
Abstract: Objective : The main aim of this study was to evaluate the presence of Streptococcus agalactiae ( S. agalactiae ) in the vagina and the amniotic fluid in pregnancies complicated by preterm prelabor rupture of membranes (PPROM). The next aim was to evaluate the incidence of S. agalactiae early onset sepsis in newborns from PPROM pregnancies, with respect to the presence of S. agalactiae in the vagina and the amniotic fluid. Methods : Singleton gestations with PPROM between 24 + 0 and 36 + 6 were included. A vaginal swab was obtained, and amniocentesis was performed at admission. The presence of S. agalactiae in the vagina and in the amniotic fluid was assessed by culture and by real-time polymerase chain reaction, respectively. Results : In total, 336 women were included. The presence of S. agalactiae in the vaginal and amniotic fluid was found in 9% (31/336) and 1% (3/336) of women. One woman had S. agalactiae in the amniotic fluid but was negative for the presence of S. agalactiae in the vaginal fluid. Early onset neonatal sepsis developed in one newborn from pregnancies complicated by the presence of S. agalactiae in the amniotic fluid. Conclusion : The presence of S. agalactiae in the vagina and amniotic fluid complicated approximately each 10th and each 100th PPROM pregnancy. Cultivation-negative findings of S. agalactiae in the vagina did not exclude the positivity of the amniotic fluid for S. agalactiae and the development of early onset sepsis in newborns.